Bildungsdisparitäten und Ethnizität: Zur schulischen Situation der Gitano-Minderheit in Spanien - Beuchling, Olaf (International Dialogues on Education Journal, 2014)
Spanish Gitanos or Calé form one of the largest Romany minorities in the EU. While they lived at the margins of Spanish society over centuries, their living and educational conditions have improved considerably within the last three decades. This article focuses on the educational situation of the Gitanos by incorporating empirical studies published on that topic in the recent years in Spain. It can be shown that the schooling of this ethnic minority has improved on the one hand, while considerable educational disparities continue to exist in comparison to the majority population on the other hand. In conclusion, some recent challenges are discussed which are of relevance for this specific case of educational inequality.